2017
DOI: 10.1038/s41598-017-04650-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reactive oxygen and nitrogen species generated in three liquid media by low temperature helium plasma jet

Abstract: In order to identify aqueous species formed in Plasma activated media (PAM), quantitative investigations of reactive oxygen and nitrogen species (ROS, RNS) were performed and compared to Milli-Q water and culture media without and with Fetal Calf Serum. Electron paramagnetic resonance, fluorometric and colorimetric analysis were used to identify and quantify free radicals generated by helium plasma jet in these liquids. Results clearly show the formation of ROS such as hydroxyl radical, superoxide anion radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
172
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(192 citation statements)
references
References 72 publications
11
172
1
Order By: Relevance
“…It is well accepted that multiple types of ROS/RNS are generated from LTP treatments 26,29 . However, the location of formation of the reactive species, and their ability to diffuse into porous surfaces and the liquid media from the gaseous plasma phase for APPJ configurations has not been as clearly established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well accepted that multiple types of ROS/RNS are generated from LTP treatments 26,29 . However, the location of formation of the reactive species, and their ability to diffuse into porous surfaces and the liquid media from the gaseous plasma phase for APPJ configurations has not been as clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…However, the location of formation of the reactive species, and their ability to diffuse into porous surfaces and the liquid media from the gaseous plasma phase for APPJ configurations has not been as clearly established. Electron paramagnetic resonance spectroscopy and proton nuclear magnetic resonance analysis have revealed that more stable species such as hydrogen peroxide are largely formed within the tube of the plasma jet, and that more reactive and transient species such as hydroxyl and superoxide tend to form in the plasma stream outside of the tube and between the nozzle of the jet and the target sample 29 . Additionally, the amounts of different types of species generated as a function of various system parameters is also under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence the interaction of atmospheric pressure plasmas with liquids was recently subject to a number of studies …”
Section: Introductionmentioning
confidence: 99%